Pengaruh Penggunaan Media Google Earth terhadap Pembelajaran Peta di Sekolah Dasar - Diaz Putri Amelia; Monica Oktafianti; Tin Rustini (Departement of Mathematics Education, 2023)
The use of technology in learning needs to be realized in real terms, because this is related to the progress of Indonesian education. However, it is very unfortunate that many learning activities in schools still seem monotonous and have not made the most of technology. One way to utilize technology in learning is to use it as media. By using digital media, it will make it easier for teachers and students to interact in class, especially on social studies learning material which has its own level of understanding and difficulty because it is social. In this study the authors used google earth media to help students understand the map material and see how students respond in learning assisted by google earth media. This research uses a descriptive-qualitative method with a case study approach. Sources of data obtained from journals and opinions of experts. The conclusion obtained from this research is that it is hoped that the use of Google Earth media can become one of the innovative and interesting media which can later motivate and improve student learning outcomes, especially in learning maps in Social Sciences subjects.